Directed energy deposition of pure copper using blue laser. (6th January 2023) - Liu, Xiao; Wang, Haoren; Kaufmann, Kevin; Vecchio, Kenneth
Abstract: Additive manufacturing (AM) technology has progressed dramatically over the last decade, allowing for rapid manufacturing of components with complex geometries and diverse feedstocks. AM of previously challenging materials such as pure copper has thus been made easier with extended processing routes. However, only powder bed-based AM processes (typically equipped with near IR lasers or an electron beam) have previously been demonstrated for producing bulk pure Cu parts with well-defined geometries, where certain disadvantages and limitations abound. This study demonstrates the first bulk Cu parts with well-defined geometries built by the blown powder, directed energy deposition (DED) process with a blue laser. Near full density (up to 99.6 %) parts with a volume of 1000 mm 3 were produced, which is the densest pure Cu part reported so far in laser AM, but at a significantly lower energy density compared to similar volume parts built using near IR lasers. A larger part with a volume of 8000 mm 3, the largest volume of pure Cu reported to date in laser AM, was also fabricated using the same build parameters with relative density up to 94.1 %. Microstructure analyses were performed and the influence of different building conditions were examined. Highlights: First pure Cu part fabricated by blue laser + DED with well-defined geometry. Near full density parts were realized with record low energy densities. Highest relative density (99.6 %, Archimedes) in laser-based AM of pure Cu achieved. Largest build volume (8000 mm 3 ) in laser-based AM of pure Cu reported to date. The effects of increasing build volume on build quality were analyzed.